A Self‐Powered Flow Velocity Sensing System Based on Hybrid Piezo‐Triboelectric Nanogenerator. Issue 5 (4th December 2022) - Ge, Chengpeng; Ma, Jijie; Hu, Yili; Li, Jianping; Zhang, Yu; He, Xinsheng; Cheng, Tinghai; Wen, Jianming
Abstract: Monitoring the flow velocity of an urban ventilation system has great significance for air circulation and air quality. In this study, a self‐powered flow velocity sensor based on hybrid piezo‐triboelectric nanogenerator (P‐TENG) is proposed. The flow velocity is detected by a triboelectric nanogenerator (TENG) working in freestanding triboelectric‐layer mode. A polyvinylidene difluoride (PVDF) fixed on the galloping beam converts the kinetic energy of the moving air into electricity. Both the TENG and PVDF are driven by the galloping vibration of a bluff body arisen from the air flow of ventilation. The structure of the P‐TENG is provided and a prototype is fabricated. The experiments indicate that the PVDF can generate 2.4 µW of energy across an external resistance of 60 MΩ. Flow velocity ranging from 4 to 10 m s −1 can be well detected by the proposed nanogenerator. Moreover, the P‐TENG is applicable to a critical environment with humidity up to 75%. Demonstration is carried out on a wind tunnel, illustrating good reliability as the frequency remains stable for the whole duration. Compared with the commercial anemometer, the error rate is under 1% after calibration. The proposed P‐TENG promises in low cost, self‐powered flow velocity monitoring in urban ventilation systems. Abstract : A self‐powered flow velocity sensor based on hybrid piezo‐triboelectric nanogenerator (P‐TENG) is proposed. The TENG adopts frequency to describe the flow velocity. It demonstrates stable performance in critical environment with humidity up to 75%. The PVDF fixed on the beam collects the flow energy. The P‐TENG promises in low cost, self‐powered flow velocity monitoring in urban ventilation systems.